Femoral artery Doppler ultrasound is more accurate than manual palpation for pulse detection in cardiac arrest. (April 2022) - Cohen, Allison L.; Li, Timmy; Becker, Lance B.; Owens, Casey; Singh, Neha; Gold, Allen; Nelson, Mathew J.; Jafari, Daniel; Haddad, Ghania; Nello, Alexander V.; Rolston, Daniel M.; ,; et al.
Abstract: Objectives: Our primary objective was to assess the accuracy of Doppler ultrasound versus manual palpation in detecting any pulse with an arterial line waveform in cardiac arrest. Secondarily, we sought to determine whether peak systolic velocity (PSV) on Doppler ultrasound could detect a pulse with a systolic blood pressure (SBP) ≥ 60 mmHg. Methods: We conducted a prospective, cross-sectional, diagnostic accuracy study on a convenience sample of adult, Emergency Department (ED) cardiac arrest patients. All patients had a femoral arterial line. During a pulse check, manual pulse detection, PSV and Doppler ultrasound clips, and SBP were recorded. A receiver operator characteristic curve analysis was performed to determine the optimal cut-off of PSV associated with a SBP ≥ 60 mmHg. Accuracy of manual palpation and Doppler ultrasound for detection of any pulse and SBP ≥ 60 mmHg were compared with McNemar's test. Results: 54 patients and 213 pulse checks were analysed. Doppler ultrasound demonstrated higher accuracy than manual palpation (95.3% vs. 54.0%; p < 0.001) for detection of any pulse. Correlation between PSV and SBP was strong (Spearman correlation coefficient = 0.89; p < 0.001). The optimal cut-off value of PSV associated with a SBP ≥ 60 mmHg was 20 cm/s (area under the curve = 0.975). To detect SBP ≥ 60 mmHg, accuracy of a PSV ≥ 20 cm/s was higher than manual palpation (91.4% vs. 66.2%; p < 0.001). Conclusions: Among ED cardiac arrest patients, femoral artery Doppler ultrasound was more accurate than manual palpation for detecting any pulse. When using a PSV ≥ 20 cm/s, Doppler ultrasound was also more accurate for detecting a SBP ≥ 60 mmHg.